THE INFLUENCE OF ENTREPRENEUR LEADERSHIP AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF THE STATE CIVIL APPARATUS - Tri Raharjanto (SEAN Institute, 2022)
The purpose of this research is to determine the extent to which leadership style and cultural norms at the Department of Population and Civil Registry of Pekanbaru City have an impact on the level of employee performance there. Descriptive statistical analysis, which takes a quantitative approach, is the method of analysis that was utilized in this particular piece of research. Through the use of questionnaires and surveys, as well as the selection of respondents at random from the total population, a total of 54 individuals provided responses. The data from the respondents were put through several statistical data processing steps before the hypothesis was put to the test. These steps included checking the validity and reliability of the data, which included making assumptions about things like normality, homoscedasticity, and multicollinearity. After that, continue with the analysis of multiple linear regressions and the t test. In addition, based on the findings of the statistical analysis, the following results were obtained: that the influence of entrepreneurial leadership factors and organizational culture had a positive and significant effect on employee performance